A comprehensive review of bacterial osteomyelitis with emphasis on Staphylococcus aureus. (November 2020) - Nasser, Ahmad; Azimi, Taher; Ostadmohammadi, Soheila; Ostadmohammadi, Samaneh
Abstract: Osteomyelitis, a significant infection of bone tissue, gives rise to two main groups of infection: acute and chronic. These groups are further categorized in terms of the duration of infection. Usually, children and adults are more susceptible to acute and chronic infections, respectively. The aforementioned groups of osteomyelitis share almost 80% of the corresponding bacterial pathogens. Among all bacteria, Staphylococcus aureus ( S. aureus ) is a significant pathogen and is associated with a high range of osteomyelitis symptoms. S. aureus has many strategies for interacting with host cells including Small Colony Variant (SCV), biofilm formation, and toxin secretion. In addition, it induces an inflammatory response and causes host cell death by apoptosis and necrosis. However, any possible step to take in this respect is dependent on the conditions and host responses. In the absence of any immune responses and antibiotics, bacteria actively duplicate themselves; however, in the presence of phagocytic cell and harassing conditions, they turn into a SCV, remaining sustainable for a long time. SCV is characterized by notable advantages such as (a) intracellular life that mediates a dam against immune cells and (b) low ATP production that mediates resistance against antibiotics. Highlights: Osteomyelitis, gives rise to two main groups of infection: acute and chronic. The aforementioned groups of osteomyelitis share almost 80% of the corresponding bacterial pathogens. S. aureus is a significant pathogen and is associated with a high range of osteomyelitis symptoms. S. aureus has many strategies for interacting with host cells including Small Colony Variant (SCV), biofilm formation, and toxin secretion. S. aureus virulence factors stimulate attachment, persistence, immune evasion, invasion, toxicity, and intracellular lifestyle.